Investigation of Dual Task Effect on the Severity of Stuttering in School-Age Children - Fahime keyhani; Akbar Darouie; Morteza Farazi; Samane Hosseinzadeh; Mohammad keyhani (University of Social Welfare and Rehabilitation Sciences, 2022)
Objective Stuttering is a speech disorder that occurs with frequent and abnormal disruptions in speech, such as sound repetition, sound prolongation, and sound or airflow blockage. Despite the many theories, the cause of stuttering has not been entirely determined, and various factors have been proposed for its etiology. According to the vicious circle hypothesis, increased speech disfluency results from hypervigilance to speech. This study aimed to measure the effect of reduced attention on speech through verbal and non-verbal dual tasks among school children with stuttering. Furthermore, the effect of dual tasks on the severity of stuttering was investigated among them. Materials & Methods In this cross-sectional study, the participants included 39 children (5 girls, 12.8%) and (34 boys, 87.2%) aged 8-12 years (10.25±1.35) with developmental stuttering selected via convenience sampling from primary schools in districts four and eight and speech therapy clinics in Tehran, Iran. Dual tasks were designed using the Visual Basic program. During the study, four speech samples were recorded for each participant. The second and third samples were designed as a dual task (addition of verbal or non-verbal tasks), while the first and fourth samples were designed as a single task. The participant's severity of stuttering in each sample was calculated based on the number of stuttered syllables (SS%), and data were analyzed by SPSS 20 software. Given the non-normal distribution of data, the generalized linear model with the Generalized Estimating Equation (GEE) and Bonferroni test were used to determine the difference in stuttering severity among speech samples. Results The GEE results showed that the severity of stuttering was different among the four speech samples (P=0.015). The lowest and highest mean stuttering severity among the 39 participants pertained to the non-verbal dual task (14.85) and the single initial task (17.11), respectively. A pairwise comparison of stuttering severity showed that the mean severity in the final single task was significantly lower than in the single initial task (P<0.05). However, mean stuttering severity was not significantly different between verbal and non-verbal tasks (P>0.05). Conclusion The findings showed that stuttering severity reduces when children with stuttering perform dual tasks. In other words, focusing children's attention on verbal and non-verbal tasks while talking reduced their dysfluency.